Risk assessment before allogeneic hematopoietic cell transplantation for older adults with acute myeloid leukemia. Issue 5 (October 2013) - Sorror, Mohamed L; Appelbaum, Frederick R
Acute myeloid leukemia (AML) most commonly affects patients older than 60 years. Outcomes of treatment of older AML patients have been poor. The advent of reduced-intensity conditioning (RIC) regimens made allogeneic hematopoietic cell transplantation (HCT) an available treatment option with curative intent for older AML patients. Because older patients are often excluded from clinical trials, little is known about the stratification of their risks before allogeneic HCT. While recent studies of RIC and allogeneic HCT have shown little impact of age on outcomes, other variables such as the recipient health status and the AML disease status and chromosomal aberrations have proven to be of prognostic significance. Here, the authors review recent studies of allogeneic HCT for older patients with AML with detailed evaluation of risk factors for relapse as well as non-relapse mortality. The authors have integrated the currently available information on transplant risks into a five-category risk–benefit system that could aid in the decision-making in this patient population.